2010
DOI: 10.1111/j.1526-4637.2010.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A for Treatment of Allodynia of Complex Regional Pain Syndrome: A Pilot Study

Abstract: Intrademal and subcutaneous administration of BoNT-A into the allodynic skin of the patients with complex regional pain syndrome (CRPS) failed to improve pain and was poorly tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Analytically, Ranoux et al 11 investigated analgesic effect of BTX-A in 29 patients with focal painful neuropathies and mechanical allodynia using a randomized, double-blind, placebo-controlled design. 13 With regard to PHN, available data from case series 5,9,10 and randomized controlled trials 11,14,15 uniformly converge to the conclusion that BTX-A has a definite therapeutic benefit in this subgroup of neuropathy patients. Investigators concluded that BTX-A may induce direct analgesic effects in patients with chronic neuropathic pain independent of its effects on muscle tone, suggesting for the first time BTX-A as a novel indications for analgesia.…”
Section: Discussionmentioning
confidence: 97%
“…Analytically, Ranoux et al 11 investigated analgesic effect of BTX-A in 29 patients with focal painful neuropathies and mechanical allodynia using a randomized, double-blind, placebo-controlled design. 13 With regard to PHN, available data from case series 5,9,10 and randomized controlled trials 11,14,15 uniformly converge to the conclusion that BTX-A has a definite therapeutic benefit in this subgroup of neuropathy patients. Investigators concluded that BTX-A may induce direct analgesic effects in patients with chronic neuropathic pain independent of its effects on muscle tone, suggesting for the first time BTX-A as a novel indications for analgesia.…”
Section: Discussionmentioning
confidence: 97%
“…Based on one class III study showing negative results [38] in conflict with 1 class III study [39] and two class IV studies [40,41] showing positive results, there is level U (insufficient) evidence for use of BoNT in the management of pain associated with CRPS (Table 6). …”
Section: Complex Regional Pain Syndromementioning
confidence: 93%
“…Safarpour et al performed a randomized, prospective, double-blind, placebo-controlled clinical trial of eight patients with CRPS (six additional patients underwent an open-label protocol) which revealed that onabotulinumtoxinA injections had no improvement in pain and were very poorly tolerated owing to i njection pain [38].…”
Section: Complex Regional Pain Syndromementioning
confidence: 98%
“…The efficacy of subcutaneous BoNT-A in relieving allodynia from chronic neuropathic pain led investigators to perform a PC-RCT on subcutaneous BoNT-A in patients with CRPS 285 . BoNT-A was injected at a dose of 5 units per site, half of the dose was injected intradermally while half was injected subcutaneously.…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 99%
“…The outcome measures included several questionnaires and quantitative sensory testing. The study had to be stopped after an interim evaluation showed no relief at 3 or 8 weeks after treatment and 8 of 9 patients considered the treatment to be intolerable and stated that they would not consider the injections as treatment for their pain 285 .…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 99%